Ser viajante: do consumo do tempo aos modos de consumo da experiência - Silva, Priscila Azeredo da (2012)
This study proposes a reflection about what is to be a traveler based on the discussion about travel, time, consumption and media. The last-mentioned has an important role in shaping the tourist gaze and the traveler being by providing image representations that constitute reference to the consumption of touristic experiences. In order to examine the tourist gaze, we establish a media as an object of analysis: the Lonely Planet travel magazine. This magazine proposes a different approach than other publications, presenting a point of view beyond the conventional, typical of the entitled "independent traveler". Editorials of 2009 and 2010 were selected with the aim to understanding the touristic gaze offered by the media. We also analyzed five publications in the section "Postais: onde você esteve e o que você viu ("Postcards: where have you been and what have you seen" in free translation) to help us understand the traveler being from the experience of the readers, and at the same time, the magazine conception about this subject. This work revealed itself to be an open reflection, offering various viewing angles, where the traveler being is not only a consumer of trip, but a consumer of time, experience and image representations that show us the anguish of the end and reveal a world worried about to give a sense to the time who flows against our will.